2015
DOI: 10.3389/fnins.2015.00238
|View full text |Cite
|
Sign up to set email alerts
|

Marked effects of intracranial volume correction methods on sex differences in neuroanatomical structures: a HUNT MRI study

Abstract: To date, there is no consensus whether sexual dimorphism in the size of neuroanatomical structures exists, or if such differences are caused by choice of intracranial volume (ICV) correction method. When investigating volume differences in neuroanatomical structures, corrections for variation in ICV are used. Commonly applied methods are the ICV-proportions, ICV-residuals and ICV as a covariate of no interest, ANCOVA. However, these different methods give contradictory results with regard to presence of sex di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
108
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 49 publications
12
108
2
4
Order By: Relevance
“…However, in our discussion we focus on the results for raw volumes, as we were mainly interested in how subregion volumes change over time, and how these longitudinal developmental patterns are associated with sex and general cognitive ability. First, previous results show that whether and how one includes a global variable like ICV in the statistical analyses may directly influence regional results in complex ways (Dennison et al, 2013;Pintzka, Hansen, Evensmoen, & Håberg, 2015;Sanfilipo, Benedict, Zivadinov, & Bakshi, 2004). Second, recent results also show that global metrics, including ICV, continue to change in late childhood and adolescence (Mills et al, 2016) and controlling for these measures in developmental studies thus generates a different research question of relative change.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our discussion we focus on the results for raw volumes, as we were mainly interested in how subregion volumes change over time, and how these longitudinal developmental patterns are associated with sex and general cognitive ability. First, previous results show that whether and how one includes a global variable like ICV in the statistical analyses may directly influence regional results in complex ways (Dennison et al, 2013;Pintzka, Hansen, Evensmoen, & Håberg, 2015;Sanfilipo, Benedict, Zivadinov, & Bakshi, 2004). Second, recent results also show that global metrics, including ICV, continue to change in late childhood and adolescence (Mills et al, 2016) and controlling for these measures in developmental studies thus generates a different research question of relative change.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, prior studies found inconsistent morphometry with and without correction for ICV, with one study finding opposites results when adding sexual dimorphic covariates to their ANCOVA analysis (Pintzka et al 2015). To address this, we ran our analyses with and without correcting for ICV and the majority of our results remained significant when co-varying for ICV.…”
Section: Discussionmentioning
confidence: 97%
“…To identify specific brain regions with significant lGI effects, we used cluster-wise correction for multiple comparisons from Monte Carlo simulation with 10,000 iterations (Pintzka et al, 2015; Royle et al, 2013). Clusters were initially obtained using a p < 0.001 (two-tailed) vertex-wise threshold, and then reported only if they met additional cluster-wise probability of p <0.05 (two-tailed).…”
Section: Methodsmentioning
confidence: 99%